The Familial Aggregation of Cigarette Smoking in Kish, Iran - Mansouri, A (Kowsar, 2012)
BACKGROUND: Based on WHO reports, smoking is an epidemic in developing countries. One of important issues about this behavior is its distribution pattern in family members. The main purpose of this study was to evaluate if cigarette smoking had a tendency to cluster or aggregate in the families and what the determinants were. METHODS: Using a multi-stage random cluster sampling approach, a household survey was conducted in Kish Island in 2009. We used the Alternating Logistic Regressions algorithm to model to show the familial aggregation. RESULTS: The odds ratio for the aggregation of cigarette smoking between family members was 1.63 (1.29-2.06) which increased to 1.96 (1.50-2.55) after adjustment for demographic factors. There was no significant correlation between siblings' cigarette smoking nor was between spouses but the pairwise odds ratio for parents offspring was significant. In other words, cigarette smoking in at least one of the parents increased the odds of being a smoker in offspring significantly. CONCLUSION: The study showed that the smoking behavior aggregated in families significantly. The inter-parent offspring aggregation was the main component of the familial aggregation. Higher education and age-gender interaction were determinants of smoking in the families. The programs for prevention and cessation of this behavior in the community might be more successful if they were designed in a family-based rather than an individual-based approach.